1984
DOI: 10.1172/jci111580
|View full text |Cite
|
Sign up to set email alerts
|

2'-deoxyguanosine toxicity for B and mature T lymphoid cell lines is mediated by guanine ribonucleotide accumulation.

Abstract: Abstract. Inherited deficiency of the enzyme purine nucleoside phosphorylase (PNP) results in selective and severe T lymphocyte depletion which is mediated by its substrate, 2'-deoxyguanosine. This observation provides a rationale for the use of PNP inhibitors as selective T cell immunosuppressive agents. We have studied the relative effects of the PNP inhibitor 8-aminoguanosine on the metabolism and growth of lymphoid cell lines of T and B cell origin. We have found that 2'-deoxyguanosine toxicity for T lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 28 publications
3
19
0
Order By: Relevance
“…GTP levels doubled over 24 h (Table II) tivity of T lymphoblasts to 2'-deoxyguanosine is associated with the capacity of the T phenotype for accumulation of deoxyribonucleotides. B lymphoblasts (JP), as previously reported (29), failed to elevate their dGTP or dATP pools significantly. Effectofcoincubation with2-deoxycytidine.…”
Section: Resultssupporting
confidence: 55%
See 3 more Smart Citations
“…GTP levels doubled over 24 h (Table II) tivity of T lymphoblasts to 2'-deoxyguanosine is associated with the capacity of the T phenotype for accumulation of deoxyribonucleotides. B lymphoblasts (JP), as previously reported (29), failed to elevate their dGTP or dATP pools significantly. Effectofcoincubation with2-deoxycytidine.…”
Section: Resultssupporting
confidence: 55%
“…Catabolism of 2'-deoxyguanosine and salvage to guanine ribonucleotides is an important cause of its toxicity to B lymphoblasts and mature T cell lines, but not for HGPRTase-deficient B cell lines or PNP-inhibited T lymphoblasts (29,39). In our experiments with T lymphoblasts GTP was not increased by 2'-deoxyguanosine concentrations that caused GI-phase arrest, and we have found that HGPRTase-deficient T lymphoblasts similarly block in GI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7][8] It was postulated that this effect is caused by intracellular enzymatic phosphorylation of deoxyguanosine to its monophosphate, diphosphate, and, finally, triphosphate (dGTP), which acts as an allosteric inhibitor of ribonucleoside reductase. [16][17][18] Therefore, the cytotoxic effects of mononucleotides on different cell lines may occur not only as the result of their dephosphorylation, but also as a consequence of their effective transport across cell membranes. Some nucleoside carriers responsible for cellular uptake of nucleosides can be inhibited by NBTI, dilazep, or dipyridamole.…”
Section: Role Of Nucleoside Transporters In Cytotoxic Effects Of Nuclmentioning
confidence: 99%